Host Response to Development of Sports Tourism in Kazan, the Republic of Tatarstan - Kamaletdinova, Guliia (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Sports tourism as one of the fastest developing segments of the tourism industry has the potential to bring noticeable social, economic and environmental impacts to the hosting destinations. This thesis examined the percieved impacts of sports tourism and mega-sports events on the residents of Kazan in the Republic of Tatarstan. The study used a qualitative approach to achieve a detailed study of the research area. The data for this research was obtained through semi-structured interviews with 32 residents who were selected through purposeful sampling and interviewed in detail. Data was analysed through thematic analysis. The analysis of the host response to sports tourism in Kazan showed that the locals believed that there were both positive and negative impacts of sports tourism and mega sporting events in the area. Further, the results show that even though there were negative impacts of tourism, the host communities’ overall perception of the impacts of tourism were more positive that negative. Thus, the local community believed that positive impacts were greater than negative impacts. The main conclusion drawn is that, since the host population believed that sports tourism development brought more benefits than costs to the community, then they were in support of the further development of sports tourism in their community. Social exchange theory has established the theoretical basis for many studies looking at the host’s response to tourism as was the case in this study. Keywords: Sports Tourism, Sporting Mega-event, Kazan, Republic of Tatarstan, FIFA World Cup, Universiade, Russian Federation, Residents Perception, Economic Impacts, Social Impacts

ÖZ: Turizmin en hızlı gelişen kesimlerinden biri olan spor turizminin ev sahibi ülkelere gözle görülür bir şekilde sosyal, ekonomik ve çevresel bakımdan etki etme potansiyeli vardır. Bu tezde spor turizminin ve büyük etkinliklerin Tataristan Cumhuriyeti’nde bulunan Kazan’ın sakinleri üzerindeki etkileri incelemektedir. Bu tezde araştırma alanı üzerine nitel araştırma yapılmaktadır. Araştırma için veriler amaçlı örnekleme kullanılarak seçilen 32 Kazan sakini ile yarı yapılandırılmış görüşmeler sayesinde toplanmıştır. Bu veriler tematik analiz kullanılarak incelenmiştir. Kazan sakinleri ile gerçekleştirilen görüşmeler yerlilerin bölgedeki spor turizminin ve büyük etkinliklerin bölgeye hem olumlu hem de olumsuz etki ettiğini düşündüğünü göstermektedir. Aynı zamanda yerel halkın turizmin etkisini olumsuzluktan fazla olumluluk olarak değerlendirdiği görülmektedir. Araştırmadan çıkan ana sonuç, yerli halkın spor turizmini zararlıdan çok yararlı olarak gördüğü için spor turizminin daha da çok gelişimesini desteklemeleridir. Yerli halkın turizme olan bakış açısını ölçen birçok çalışmada olduğu gibi bu araştırmada da sosyal değişim teorisi, teorik altyapı olarak kullanılmıştır Anahtar Kelimeler: Spor Turizmi, Büyük Etkinlikler, Tataristan Cumhuriyeti, FİFA Dünya Kupası, Universiade, Rus Federasyonu, Bölge Sakinlerinin Algısı, Ekonomik Etkiler, Sosyal Etkiler
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Assist. Prof. Dr. İlkay Yorgancı.
Keywords: Tourism; Sports and Tourism--Economic Aspects; Sports--Travel--Tourism; Hospitality industry--Sports--Tatarstan; Sports Tourism; Sporting Mega-event; Kazan; Republic of Tatarstan; FIFA World Cup; Universiade; Russian Federation; Residents Perception; Economic Impacts; Social Impacts